2006
DOI: 10.1073/pnas.0606805103
|View full text |Cite
|
Sign up to set email alerts
|

Follicle-stimulating hormone stimulates TNF production from immune cells to enhance osteoblast and osteoclast formation

Abstract: Declining estrogen production after menopause causes osteoporosis in which the resorption of bone exceeds the increase in bone formation. We recently found that mice deficient in the ␤-subunit of follicle-stimulating hormone (FSH␤) are protected from bone loss despite severe estrogen deficiency. Here we show that FSH␤-deficient mice have lowered TNF␣ levels. However, TNF␣-deficient mice are resistant to hypogonadal bone loss despite having elevated FSH, suggesting that TNF␣ is critical to the effect of FSH on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
136
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 196 publications
(151 citation statements)
references
References 39 publications
12
136
3
Order By: Relevance
“…We discovered that FSH directly stimulates bone resorption by osteoclasts [8,9]. Several studies have confirmed direct effects of FSH on the skeleton in rodents and humans.…”
Section: Follicle Stimulating Hormonementioning
confidence: 89%
See 1 more Smart Citation
“…We discovered that FSH directly stimulates bone resorption by osteoclasts [8,9]. Several studies have confirmed direct effects of FSH on the skeleton in rodents and humans.…”
Section: Follicle Stimulating Hormonementioning
confidence: 89%
“…In a separate study, FSHR activation was shown to enhance RANK receptor expression [20]. In addition, FSH indirectly stimulates osteoclast formation by releasing osteoclastogenic cytokines, namely interleukin 1β (IL-1β), tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) in proportion to the surface expression of FSHRs [9,21]. In a study of 36 women between the ages of 20 and 50 years, serum FSH concentrations correlated with circulating cytokine concentrations [21,22].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…In addition to its action on bone and fat cells, we found previously that FSH directly upregulates the production of the inflammatory cytokine TNFα (27). Mice genetically deficient in FSHβ thus showed reduced TNFα production from bone marrow macrophages (27).…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al independently show that FSH stimulates osteoclastogenesis, which is abolished in mice lacking immunoreceptor tyrosine-based activation motif (ITAM) adapter signaling molecules (11). FSHR activation also enhances receptor activator of nuclear factor kappa-B (RANK) receptor expression (29), and indirectly stimulates osteoclast formation by releasing IL-1β, TNF-α, and IL-6 (30,31). Serum FSH levels thus correlate with circulating cytokine concentrations (32).…”
Section: Discussionmentioning
confidence: 99%